Subjectivity in Caring for the Human Condition. Existential Ideas of Paul Tillich as an Inspiration for Pedagogy - Julita Orzelska (Nicolaus Copernicus University in Toruń, 2020)
The article discusses the issue of subjectivity in caring for the valuable existence of the individual. While following the ideas of Paul Tillich, I appeal for a widening of the interpretation space in pedagogical thought, by applying concepts from outside the canon's framework. The use of Tillich's analysis helps to affirm the autonomy of a person, with their centrality, and the right to remain unaffected by the pressure of collective conventions; this contributes to self-actualization and happiness. The examination of views by the great Protestant humanist Paul Tillich is extremely important and much needed for pedagogy, as it inspires the shaping of existential sensitivity in the course of formation and education, while taking care of individuals.